Tour Operating Business - Yarcan, Sukru (Istanbul University Press, 2021)
Tourist product is composed of an amalgam of services and products that are brought together to create an overall tourist experience. This multi-service product, by definition, includes a trip away and an overnight at the destination, and can either be created by the tourists themselves or by a tour operator. Travel trade is an important sector of the tourism industry responsible for packaging travel services and offering them to potential travelers. They also have an important role in commercialization of tourist products and destination development. Tour packages are usually cheaper, safer and more convenient for tourists. Hence, travel firms create the link between tourist products at the destination and the travelers. Tour operators even create and brand destinations. They take various risks and invest in the destination product ahead of the sales, hence they are an important stakeholder for tourism destination development. Despite there being extensive literature on transportation, accommodation, restaurants, attractions and events; the tour operators, their place in tourism system and their operations are neglected in education and research. This book addresses this gap both in theory and practice. The first chapter discusses the nature of the tourism industry and tourism supply. Tourism resources, tourism types, tourist services and organizations are also explored in this section. The second chapter focuses on the tourist product, features of tourism as a service, standardization and distribution of tourism products. This chapter also introduces travel firms as both producers and intermediaries of tourism products and services. The third chapter focuses on the travel industry, defining travel agencies and tour operators. Differences between the two and different types of each are also detailed in this section. This book also recognizes tour guides as an important part of the tourism industry and a significant partner to travel firms. Tour guides, their roles, certification and their relationships with tour operators are examined in chapter four. Tourism education, its significance, characteristics and challenges are provided in chapter five. Chapter six delves into tour operation, its management and stages. The importance of tour operators for destination development, sustainability, branding and competition and their relationships with other stakeholders are examined in this chapter. Chapter six also explores ICT information and communication technology tools in tour operation, disintermediation and online travel agencies. This book is designed as a comprehensive destination management book as well. Hence the second part of the book delves into multinational tourism organizations, tourism types and offers case destinations for further discussion. The seventh chapter focuses on multinational corporations that invest in travel trade, including financial institutions. Vertical and horizontal integration in the industry and different types of investors are also examined in this chapter. Business travel and MICE tourism are discussed in chapter eight and nine. Their characteristics, types, operation, destination and choice factors are examined supported with sample itineraries, promotion kits and SWOT analysis. Faith tourism is another tourism type, explored in chapter ten. Istanbul and Anatolia as faith tourism destinations and their relationship with tourism are explored from the perspective of different stakeholders. Chapter eleven delves into culture tourism, which is another significant tourist segment for tour operators. Culture tourism is explored from the perspective of Istanbul and its cultural resources. This book, in chapter twelve, also makes a comparison between two popular destinations in Turkey: Antalya, the major leisure destination and Istanbul, the center for business travel and cultural tourism. The book finally concludes with an epilogue discussing the geopolitical dimensions of tourism and tourist flows. As both authors are scholars with hands on experience in tour operation, who integrated theory with practice within the book and provided real life examples, illustrations and itineraries. It is very much hoped that the content will provide both theoretical and practical contributions and will be a useful resource for tour operator education and training.